The next steps to develop innovation ecosystem in Azerbaijan: the case of Innoland acceleration and incubation center - Aghayeva, Nazrin (ADA University, 2021)
Innovation ecosystem is the network of public and private organizations which stimulates the creation of disruptive technologies, spurs the change and promotes sustainability of economic growth in the country. Innoland Incubation and Acceleration Center is one of the responsible bodies of the government to improve the ecosystem, encourage application of smart tools within the organizations, support entrepreneurs and commercialize their products. Despite its 3 years of operation, Innoland has been able to be very successful in the ecosystem with strong cooperation, organization of events and attraction of investments. Yet, in the recent period, the long term effectiveness of the activities of Innoland is under the question. Therefore, this paper analyzes the external and internal factors affecting the operation of Innoland and gives recommendations on where to make improvements to contribute to the development process of the ecosystem in the long term.
Improving effectiveness of Innoland
Keywords: Business; Innovation ecosystem; Innoland Incubation; Ecosystem--Azerbaijan